THE EFFECTIVENESS OF THE SIPRAJA APPLICATION FOR IMPROVING PUBLIC SERVICES IN KLUDAN VILLAGE, TANGGULANGIN DISTRICT, SIDOARJO REGENCY - Amelia, Vira; Rodiyah , Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of e-government implementation through the Sidoarjo People’s Service System (SIPRAJA) in managing population documents in Kludan Village. Method: A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model to capture the dynamics of implementation. Results: The findings show that SIPRAJA has enhanced the efficiency of population administration services by reducing queues, accelerating service completion times, and strengthening transparency and accountability. Despite these improvements, several challenges persist, including uneven internet access, limited digital literacy among community members, and technical barriers in application operations. Nevertheless, socialization and training initiatives by the village government have helped improve public knowledge and participation in using SIPRAJA. Novelty: This study provides empirical insights into the role of SIPRAJA as a digital innovation at the village level, highlighting its potential as an inclusive and sustainable solution for improving population administration services, while also identifying key areas for further development in infrastructure, management responsiveness, and digital literacy.